The rise and fall of executive functions in high-level football players - Beavan, A.; Spielmann, J.; Mayer, J.; Skorski, S.; Meyer, T.; Fransen, J. (Psychology of Sport and Exercise, 2020)
Introduction: Executive functions are higher-level cognitive functions. Despite being relevant to many aspects of everyday life, it is contentious whether executive functions are important for high performing athletes. Executive functions increase throughout the career of an athlete, yet it remains unknown what are the main contributors. Therefore, this study examined the effect of age and experience on executive functions in a cohort of high performing football players.